Image of Self Compassion on Space Officers at Eltari Airport - Reni Kurniati; M.K.P. Abdi Keraf; Yeni Damayanti (Journal of Health and Behavioral Science, 2022)
Self-compassion is an attitude of having concern and kindness towards oneself when faced with various difficulties in life. In the field of work, which has the function and duty to regulate the smooth operation of civil aviation, pretending space employees are required not to make the slightest mistake. So employees need to have self-compassion themselves. This study uses a qualitative method, with the techniques of observation, interviews, and documentation. The participants were 8 employees of the temple space. In general, participants in this study tend to have good self-compassion. This is illustrated by the ability of self-kindness, mindfulness, and common humanity, as well as low self-judgment, isolation, and over-identification by participants at this time.